The Influence of Sharia Banking Advertising and Promotion on SMKN 8 Garut Teachers' Interest in Choosing Sharia Banks - Redmon Windu Gumati; Dadang Saripudin (Penerbit Hellow Pustaka, 2024)
This research aims to find out whether advertising and sales promotion variables influence the interest in saving SMKN 8 Garut teachers at Sharia Banks. This research uses quantitative methods and is associative. Data analysis using multiple linear regression with the SPSS 21 for windows application. Meanwhile, data collection uses questionnaires (questionnaires). The sampling technique in this study used purposive sampling techniques. The population in this study were teachers at SMKN 8 Garut. The results of this research show that the t test of advertising variables has a positive and significant effect on teachers' interest in saving with a t count value of 4.311> 1.97 t table, which means that t count > t table. The t test on the sales promotion variable had a positive and significant effect on the teacher's saving interest with a calculated t score of 9,629 > 1.97 t table, which means that t calculated > t table. And for the f test, f count was obtained at 120,708 and f table 3.04, f count > f table which means that the variables advertising and sales promotion together have a positive and significant effect on teachers' interest in saving at Sharia Banks. Meanwhile, the determination coefficient (R2) is 0.531, which means that the contribution of advertising and sales promotion variables is only able to explain the Teacher savings interest variable of 53.1%. Meanwhile, the remaining 46.9% was explained by other variables.